Surgical treatment of posttraumatic ankylosis of the TMJ with different pathogenic mechanisms - Baykul, Timucin; Aydin, Mustafa Asim; Nasir, Serdar Nazif; Toptas, Orcun (European Journal of Dentistry, 2012)
Objectives: Posttraumatic ankylosis of the TMJ can be caused by many different pathogenic mechanisms. Prosthetic alloplastic grafts and autogenous grafts are the options for surgical treatment.Methods: Seven patients were examined clinically and radiologically. Autogenous interpositioners were used for treatment of TMJ ankylosis.Results: No major complications were seen after surgery. Interincisal distances have significantly widened following mouth opening exercises for one year.Conclusions:Human skulls have many structure and shape differences, so it is difficult to replace a jaw joint successfully with an artificial one. Using autogenous tissues seems an appropriate choice for treatment. (Eur J Dent 2012;6:318-323)
Keywords: Ankylosis; TMJ; trauma